Augmented Reality Research in Middle Schools: Bibliometric Review - Fadli Agus Triansyah; Mitrayana Mitrayana; Fitri Yanti; Andi Rabuandika; Ilham Muhammad (LP. Ma'arif Janggan Magetan, 2023)
Augmented Reality is a technology that helps 3D virtual objects to be viewed interactively in the real world. Implementing Augmented Reality into the learning process has a great opportunity to get various benefits. The purpose of this study is to capture research landscapes related to Augmented Reality in high school learning from 2009 to 2023. The method used is bibliometric analysis. The database used in collecting the necessary related information is the Scopus database. Augmented Reality research publications in secondary schools from 2009 to 2023 have experienced an increase in recent years. The highest number of citations was in 2013. The United States and China are the most influential countries in this field. The focus of research related to Augmented Reality in secondary schools is 1) technology, motivation, and environment; 2) games and interests; 3) achievement and development. The keyword Augmented Reality is not directly related to science learning. The game keywords are not directly related to the outcomes keywords. This novelty can be useful for further research examining a theme similar to this research. The new themes related to this field are science learning, mathematics education, concepts, and spatial abilities.